The Effectiveness of the Implementation of Inclusive Education in Mainstream Schools: A South African Perspective - Malahlela Moyagabo Kate; Sadiki Marubini Christinah (Journal of Education, Society & Multiculturalism)
The onset of the South African democratic government in 1994 brought remarkable changes in the entire education due to the introduction of an inclusive education system. This study argues that although the implementation of inclusive education is currently mandatory, the world over its effectiveness in South Africa is not yet established. The study aimed to explore teachers’ perceptions of the effectiveness of implementing inclusive education in their mainstream schools. The study used a phenomenological qualitative research design. In-depth semi-structured interviews were used to collect the data. Ten (10) teachers from five (5) mainstream secondary schools were purposively selected based on their years of teaching experience, knowledge about inclusive education, and relevant qualifications. The data gathered through interviews were analysed using qualitative content analysis. The analysed data came up with three themes: 1) Inclusive education policy implementation, 2) Inclusive teaching and learning strategies, and 3) Intervention by the Department of Education. Findings point to teachers’ lack of self-efficacy, inadequate support from district-based support teams, and challenges in supporting learners with disabilities. The study recommends in-service training and ongoing professional development for all mainstream teachers, provision of adequate resources, equipment, and assistive devices for learners with disabilities, and inclusive education policy implementation. This study contributes to knowledge of the challenges faced by teachers in their attempts to implement inclusive education and to support learners with and without disabilities in mainstream schools.